Parent awareness and perceived barriers regarding hearing impairment among school age children in Taif Region of Saudi Arabia - Yahya A Fageeh; Manar H Alghoribi; Maryam M Albishi; Atheer A Alshanbari; Amjad A Alqethami; Tethkar M Altowairqi; Norah K Alosaimi (Wolters Kluwer Medknow Publications, 2023)
Background: Hearing impairment (HI) is the most common global disabling condition. It is a considerable public health condition in childhood that is associated with long-term socio-emotional-academic, and communication difficulties. The current study explored the knowledge and awareness of HI among school-age children and its related factor in Taif, Saudi Arabia. Materials and Methods: A cross-sectional study was done on 268 Saudi school-age children in the population of the Taif region of Saudi Arabia. A predesigned questionnaire was used to collect their demographic data, consanguinity, education level, and academic performance. Results: About 45.9% of parents had good awareness related to hearing loss and its impact on children's life. Only 19% (n = 51) of parents reported that their children encountered language problems in communicating with others. When we assessed the relationship between this language problem and academic performance, it was found that children with language problems had below-average academic performance (P < 0.001). Conclusion: The study showed that parents' awareness about children's hearing was not that satisfactory, and there was a considerable amount of difficulties faced by the children in their personal and social life due to these hearing problems. It is imperative to create awareness among the public regarding various modifiable risk factors of HI by conducting health awareness campaigns.